Effects of extended heating time and post-urea treatment on formaldehyde emission and properties of phenolic Compreg rubberwood - Ashaari, Zaidon; Lee, Seng Hua; Halis, Rasmina; Shaari, Roslinda; Omar, Mariani Ayu; Shobari, Shuhaibah (Universiti Putra Malaysia Press, 2015)
Effects of post-urea treatment and extended heating time after compregnation on the formaldehyde emission and properties of rubberwood were investigated in this work. Rubberwood strips having nominal dimensions of 150 mm x 50 mm x 5 mm were compregnated with medium molecular weight phenol formaldehyde (MmwPF, mw 2,000) and low molecular weight phenol formaldehyde (LmwPF, mw 600), respectively. Compregnated rubberwood were then soaked in urea solutions in different concentrations of 10%, 20% and 40%, respectively, for 1 minute. Extended heating times of 0, 12, and 24 hours under 100 ± 2°C were applied to another set of rubberwood compregnated with LmwPF. Properties such as formaldehyde emission, mechanical and physical properties were also tested. Results showed that the post-urea treatment and extended heating time reduced the formaldehyde emission of the compregnated rubberwood. However, mechanical strength of compregnated rubberwood was not significantly affected by both the treatments. Improvements in water absorption (WA) and thickness swelling (TS) of compregnated rubberwood were observed when the heating time was lengthened. Nevertheless, the formaldehyde emission obtained is still far beyond the standard threshold limit of 0.16 – 2.0 mg/l. Thus, further study has to be conducted by lengthening the heating time and increasing the concentration of urea solution.